The Effectiveness of Bibliotherapy Using Flipbooks in Enhancing Resilience among Adolescents in Fatherless Situations - Utari Pratiwi; Yarmis Syukur (Bisma The Journal of Counseling, 2025)
The fatherless phenomenon experienced by adolescents has implications for low emotional resilience, thereby increasing vulnerability to psychosocial stress, anxiety, and reduced mental well-being. This study aims to examine the effectiveness of bibliotherapy using digital flipbook media in enhancing the emotional resilience of adolescents in fatherless situations. The research employed a quantitative approach with a one-group pretest-posttest pre-experimental design. The sample consisted of 20 seventh-grade junior high school students selected through purposive sampling. The instrument used was a resilience questionnaire comprising 60 valid and reliable statements (α = 0.975). Data were analyzed using N-Gain and Wilcoxon tests. The results indicated a significant increase in students’ resilience after receiving flipbook-based bibliotherapy intervention. N-Gain scores ranged from 0.37 to 0.92, categorized as moderate to high, while the Wilcoxon test yielded T1 = 0 and T2 = 1614, indicating a significant difference between pretest and posttest scores. These findings demonstrate that flipbook-based bibliotherapy effectively strengthens emotion regulation, fosters optimism, and enhances adaptive coping mechanisms in fatherless adolescents. The study underscores the importance of integrating innovative digital media into school counseling services as a preventive and curative effort to improve adolescent mental health.